MAIN PROBLEMS AND PRINCIPLES OF EDUCATION INNOVATION NATURAL - О. Плахотник; Т. Захарук; К. Янковски (Київський національний університет імені Тараса Шевченка, 2015)
Modernization of an education system requires its novation research as interdisciplinary branch of scientific knowledge. Fundamental principles of innovation education should be assumed as a basis of analysis of new functions and new content of naturalists' education. In the context of new paradigm naturalists' education should become personally significant factor owing to deep, substantial, cognitive and methodological potential of its bases.Fundamental education must be integral, that's why separate disciplines are examined not as totality of traditional autonomous courses, and they are integrated in the only cycles of disciplines and associated with a total objective function and interdisciplinary relationships.The main goal of natural science training of students in the humanities should be seen as the disclosure of the contents of holistic outlook on the basis of interdisciplinary synthesis and evolutionary-synergetic paradigm.

Модернізація системи освіти потребує дослідження її інноватики як міждисциплінарної галузі наукового знання. Основні принципи інноваційної освіти повинні бути покладені в основу аналізу нових функцій і нового змісту природознавчої освіти.У рамках нової парадигми природознавча освіта може й повинна стати соціально й особистісно значимим чинником, завдяки величезному змістовному, пізнавальному, світоглядному й методологічному потенціалу її засад.
ОСНОВНІ ПРОБЛЕМИ ТА ПРИНЦИПИ ІННОВАЦІЙНОЇ ПРИРОДОЗНАВЧОЇ ОСВІТИ
Keywords: природознавча освіта; принципи; функції природознавчої освіти; інновації; парадигма освіти; модернізація системи освіти.; Natural education; principles; functions Natural education; innovation paradigm of education; modernization of education.